2012
DOI: 10.5006/i0010-9312-68-6-475
|View full text |Cite
|
Sign up to set email alerts
|

Galvanic Corrosion and Inhibition of GW103 and AZ91D Mg Alloys Coupled to an Al Alloy in an Ethylene Glycol Solution at Ambient and Elevated Temperatures

Abstract: The galvanic corrosion of GW103 and AZ91D coupled to an Al alloy (Al 7005 [UNS A97005]) in an ethylene glycol (EG [C 2 H 6 O 2 ]) solution at ambient (25°C) and elevated temperatures (90°C) was investigated using open-circuit potential (OCP), coupling potential (CP), galvanic current density, potentiodynamic polarization curve, and electrochemical impedance spectroscopy (EIS). Moreover, weight-loss measurement and scanning electron microscopy (SEM) also were used to investigate the galvanic corrosion damage o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Inhibition was ascribed to a synergistic influence of the organic and inorganic compounds. Inhibition of the inhibitor combination decreased dramatically when a Mg alloy was coupled with other metals . In some cases, the inhibitor combination worsened the galvanic corrosion of the Mg alloys .…”
Section: Inhibitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition was ascribed to a synergistic influence of the organic and inorganic compounds. Inhibition of the inhibitor combination decreased dramatically when a Mg alloy was coupled with other metals . In some cases, the inhibitor combination worsened the galvanic corrosion of the Mg alloys .…”
Section: Inhibitionmentioning
confidence: 99%
“…In some cases, the inhibitor combination worsened the galvanic corrosion of the Mg alloys . In another case, it caused a reversal of the anode and cathode . Huang et al found that some organic inhibitors, such as piperazine and pyrazine, without mixing with an inorganic compound, can also act as an inhibitor for a Mg alloy in an ethylene glycol solution.…”
Section: Inhibitionmentioning
confidence: 99%
“…Basically, modifi cation of the environment includes increasing the pH value, reducing the concentration of aggressive species and adding passivators or inhibitors (Song, 2007a ;. Recently, some organic and inorganic inhibitors as well as combinations thereof have been developed for Mg alloys (Hu et al ., , 2012aHuang et al ., , 2012. Due to the high electrochemical activity and the presence of the corrosion product fi lm, identifi cation of a highly effi cient inhibitor for Mg is currently still diffi cult.…”
Section: Environmental Modifi Cationmentioning
confidence: 98%